Vigilancia de la morbilidad en los municipios del área de influencia durante la construcción del proyecto hidroeléctrico Porce II (Empresas Publicas de Medellín, ESP, Antioquia, 1997-2000) (2003)
ABSTRACT: This study presents the behavior of the morbidity in the four municipalities in area of influence during the construction of the hydroelectric project Porce II, as a part of the social and environmental management developed by EPM (Medellín Public Services Company) through the system of epidemiological surveillance of Porce II. The morbidity profile denotes the presence of problems associated to deficient economic and social conditions like bacterial and parasitic diseases that affect the respiratory and digestive system and the skin. In addition, the pioneer experience of this system of epidemiological surveillance generated an important contribution in the design and realization of surveillances systems on public health that allow the diagnosis of high-priority problems in the health of the populations in the influence areas during the construction of hydroelectric macro projects.